2012
DOI: 10.1037/a0024071
|View full text |Cite
|
Sign up to set email alerts
|

Assessing creativity with self-report scales: A review and empirical evaluation.

Abstract: This article reviews recent developments in the assessment of creativity using self-report scales. We focus on four new and promising scales: the Creative Achievement Questionnaire, the Biographical Inventory of Creative Behaviors, the revised Creative Behavior Inventory, and the Creative Domain Questionnaire. For each scale, we review evidence for reliability, validity, and structure, and we discuss important methodological features for users to consider. We then present new analyses of each scale based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
250
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(265 citation statements)
references
References 64 publications
3
250
0
12
Order By: Relevance
“…The Revised Creativity Domain Questionnaire (CDQ-R; Kaufman & Baer, 2004;Kaufman et al, 2010) was used to measure an individual's beliefs about his/her level of creativity in diverse domains (i.e., four domains: drama, maths/ science, arts and interaction). This scale has proved reliable and valid in previous studies to assess people's self-concept concerning their personal ability in terms of creativity (Silvia et al, 2012). Participants were asked "How creative would you rate yourself in.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Revised Creativity Domain Questionnaire (CDQ-R; Kaufman & Baer, 2004;Kaufman et al, 2010) was used to measure an individual's beliefs about his/her level of creativity in diverse domains (i.e., four domains: drama, maths/ science, arts and interaction). This scale has proved reliable and valid in previous studies to assess people's self-concept concerning their personal ability in terms of creativity (Silvia et al, 2012). Participants were asked "How creative would you rate yourself in.…”
Section: Methodsmentioning
confidence: 99%
“…For example, consistent evidence has shown that creative self-efficacy, as one of the elements of creative self-concept (Karwowski, 2015), has an effect on creative behaviour in a qualitative study (Lemons, 2010), in workplace settings (Jaussi & Randel, 2014;Tierney & Farmer, 2011), in academic settings (Beghetto, Kaufman, & Baxter, 2011)and in training programmes (Byrge & Tang, 2015). This suggests that individuals use their beliefs about their personality traits when engaging in activities, so creative self-concepts play a role in creative behaviours (Silvia, Wigert, Reiter-Palmon, & Kaufman, 2012).…”
mentioning
confidence: 99%
“…(HCAY; Raudsepp, 1981). Other self-report questionnaires ask individuals about their past creative production instead of personality traits, based on the assumption that past accomplishments can provide a dependable indication of subsequent creative accomplishments (Clapham, 2004;Colangelo, Kerr, Hallowell, Huesman, & Gaeth, 1992 Although this approach for measuring creativity has advantages of ease of use, standardized administration and scoring procedures (Runco, 2007) and high levels of reliability (see Carson et al, 2005;Davis, 1975;Gough, 1979;Hocevar, 1980;Silvia, Wigert, Reiter-Palmon, & Kaufman, 2012), it suffers from significant limitations. First, this approach mainly pays attention to personality traits, as it assumes that these could be regarded as sufficient evidence of creative ability (Barbot et al, 2011;Miller, 2014;Thompson & Lordan, 1999).…”
Section: Approaches To Measuring Creativitymentioning
confidence: 99%
“…Everyday creativity is 'defined in terms of human originality at work and leisure across the diverse activities of everyday life' (Richards, 2010, p. 190). Popular measures of everyday creativity are the revised Creative Behavior Inventory (CBI; Dollinger, 2003; based on the original CBI by Hocevar, 1979) and the Biographical Inventory of Creative Behavior (BICB; Batey, 2007) (for a review, see Silvia et al, 2012). Both inventories contain lists of various creative activities (e.g.…”
Section: Everyday Creativitymentioning
confidence: 99%